2015
DOI: 10.5558/tfc2015-044
|View full text |Cite
|
Sign up to set email alerts
|

Forestry strategies against PM2.5 pollution in Beijing

Abstract: Tree planting has been proposed by Beijing's municipal government as a measure to alleviate airborne fine particulate matter (PM) in the city as trees have large surface areas to filter pollution out of the air. To maximize this eco-efficiency, a series of active measures have been taken by the city's forestry sector. These strategies are elaborated here to provide a valuable reference for other megacities facing similar challenges.Keywords: PM 2.5 , air pollution, forestry strategies RéSuméLa plantation d'arb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Many studies have demonstrated that plants have large leaf surface areas and a complex leaf microstructure which can effectively retain dust and reduce the concentration of atmospheric particles [8][9][10][11]. Therefore, the use of urban green plants and forests to reduce and control PM pollution has attracted increasing attention around the world in recent years [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that plants have large leaf surface areas and a complex leaf microstructure which can effectively retain dust and reduce the concentration of atmospheric particles [8][9][10][11]. Therefore, the use of urban green plants and forests to reduce and control PM pollution has attracted increasing attention around the world in recent years [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Those methods have been widely used to describe disordered and irregular objects. At present, some relevant fractal theories have been used in the relevant research conducted on particle morphology in China [38,39]; however, few reports exist on the research of quantitatively characterizing particle distributions with fractal dimensions at different heights in highrise buildings. Additionally, even less research exists on Xi'an, which is located in the northwest region.…”
Section: Introductionmentioning
confidence: 99%
“…The Environmental Protection Bureau of Beijing City, as the official government agency responsible for assessing water quality in Beijing, routinely monitors some physical, chemical, and bacteriological parameters, but the monitoring program does not include the evaluation of heavy metals, pesticides and other organic compounds. In previous study, many researchers mainly focus on the reservoirs eutrophication of Beijing watersheds due to nitrogen and phosphorus pollution, and particularly, Miyun and Guanting reservoirs have been paid enough attention for the important role in Beijing social and economic development with more funds supported [13][14][15][16][17]. Meanwhile, it is necessary to provide decision-makers and audience with accurate and visualized information as distribution maps…”
mentioning
confidence: 99%